Single-grain K-feldspar pIRIR dating of the Shalongka archeological site revealed the relationship between monsoon, overbank flooding, and human occupation during the Holocene on the northeastern Tibetan Plateau. (15th December 2022) - Wang, Yixuan; Li, Guoqiang; Wang, Xiaoyan; Yan, Zhongfeng; Qin, Caixin; Yang, Jilei; Yang, He; Deng, Yanqing; Pan, Long; Chen, Chunzhu; Zhao, Wenwei; Hou, Guangliang
Abstract: The increased frequency of flooding on the Tibetan Plateau as a result of global warming has affected the lives of millions of people along the river valleys. The relationship between human settlement, climate change, and the frequency of flooding at long time scales is still unclear primarily due to the lack of a robust chronology for flooding deposits. In this study, AMS 14 C dating, single-grain quartz OSL dating, and single-grain K-feldspar pIRIR dating using pIR50 IR170 and pIR200 IR290 signals were applied to the fluvial-paleosol sequence at the archaeology site Shalongka (SLK20) in the upper Yellow River valley on the northeastern Tibetan Plateau, where Paleolithic, Neolithic, and Bronze Age cultural layers were found. Utilizing luminescence characteristics analysis and a comparison of quartz OSL ages, K-feldspar pIRIR ages, and charcoal 14 C ages, the reliability of single-grain quartz OSL and K-feldspar pIRIR ages was tested. Our results indicate that single-grain K-feldspar pIRIR170 dating with the minimum age model (MAM) can be used to date Holocene fluvial deposit that have been poorly bleached. Based on the age-depth model, proxy data of the SLK20 grain size and magnetic susceptibility demonstrate that Yellow River overbank flooding increased during the periods 9.9–9.1, ∼8.0, 7.6–6.3 and 5.0-3.4 kyr BP; during the intervals between these periods, Yellow River overbank decreased and paleosols developed. Human occupations, as indicated by the appearance of cultural layers at the SLK20 site during the ∼8.1, ∼7.8, 6.3–5.0 and 3.4–2.0 kyr BP periods, occurred when paleosol developed. The variation in East Asian summer monsoon (EASM) intensities caused a moist and warm mid-Holocene climate at the SLK20 site, which was conducive to human settlement. Flood events caused by EASM precipitation changes during the mid-Holocene significantly influenced human settlement at the SLK20 site. During the middle to late Holocene, as EASM decreased in the region, the improvement of subsistence strategies likely dominated human settlement on the northeastern Tibetan Plateau. Highlights: Poorly bleached fluvial sediment can be dated using single-grain pIR50 IR170 dating. Upper Yellow River floods occurred at 9.9–9.1, ∼8.0, 7.6–6.3 and 5.0–3.4 kyr BP. Human settlement was established at ∼8.1, ∼7.8, 6.3–5.0 and 3.4–2.0 kyr BP. Climate change, flood and subsistence strategy effect human settlement on the NE Tibetan Plateau.